2012
DOI: 10.1186/1471-2172-13-2
|View full text |Cite
|
Sign up to set email alerts
|

A selective and potent CXCR3 antagonist SCH 546738 attenuates the development of autoimmune diseases and delays graft rejection

Abstract: Background: The CXCR3 receptor and its three interferon-inducible ligands (CXCL9, CXCL10 and CXCL11) have been implicated as playing a central role in directing a Th1 inflammatory response. Recent studies strongly support that the CXCR3 receptor is a very attractive therapeutic target for treating autoimmune diseases, such as rheumatoid arthritis, multiple sclerosis and psoriasis, and to prevent transplant rejection. We describe here the in vitro and in vivo pharmacological characterizations of a novel and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…CXCL10 antibody treatment induced epidermal repigmentation in mice with established vitiligo, and therefore may offer a targeted systemic therapeutic option for patients with disease. A therapeutic strategy based on these observations may incorporate existing neutralizing antibodies or chemical inhibitors of IFNγ (51), CXCL10 (52), or CXCR3 (41, 53), or inhibitors of IFNγ or CXCL10 signaling through chemical inhibition or RNAi-induced knockdown. Completed clinical trials have tested either CXCL10 neutralization or CXCR3 blockade for psoriasis, Crohn’s disease, and ulcerative colitis, with disappointing results (41).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 antibody treatment induced epidermal repigmentation in mice with established vitiligo, and therefore may offer a targeted systemic therapeutic option for patients with disease. A therapeutic strategy based on these observations may incorporate existing neutralizing antibodies or chemical inhibitors of IFNγ (51), CXCL10 (52), or CXCR3 (41, 53), or inhibitors of IFNγ or CXCL10 signaling through chemical inhibition or RNAi-induced knockdown. Completed clinical trials have tested either CXCL10 neutralization or CXCR3 blockade for psoriasis, Crohn’s disease, and ulcerative colitis, with disappointing results (41).…”
Section: Discussionmentioning
confidence: 99%
“…The selective CXCR3 antagonist SCH 546738 attenuates the development of autoimmune diseases. 46 The CXCR3 antagonist AMG 487 exhibits inhibitory effects on lung metastasis in breast cancer. 47 In the present study, we demonstrated that JN-2 inhibits osteolytic bone metastasis of 4T1 cells with a decrease in tumor outgrowth, P65 expression, osteoclast formation, and the expression of RANKL and CXCL10.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule CXCR3 antagonists could overcome some of these challenges, and have shown efficacy in reducing inflammation in the collagen-induced arthritis (CIA) and experimental autoimmune encephalomyelitis (EAE) models, as well as prolonged allograft survival (46). Topical delivery of a selective CXCR3 antagonist could provide an improved therapeutic index, by limiting systemic exposure to immuomodulatory agents.…”
Section: Discussionmentioning
confidence: 99%